The relationship between citizen satisfaction with assessment rates & rate-related services. A case study, Mukah Division, Sarawak / Junaidi @ Saudi Narani - Narani, Junaidi @ Saudi (2016)
This study investigates the relationship between citizen satisfaction with assessment rates and rate-related services provided by Datat and Mukah District Council (DMDC) in Mukah Division, Sarawak. These services namely the general purpose services, the street lighting services, the scavenging services, and the road maintenance services are charged in the annual assessment bills. The current trend of high defaults in payment of rates is leading to substantial arreas.